Inflammatory changes in biopsy specimens from patients with suspected prostate cancer - Adamczyk, Przemysław (Polish Urological Association, 2013)
INTRODUCTION: Prostate cancer (PCa) is one of the most commonly diagnosed cancers in elderly men, and accounts for 30% of all newly diagnosed cases of cancer. The development of the ‘clinically insignificant’ prostate cancer into its invasive form is still unclear, and it is believed that chronic inflammation may play its role, as proposed by De Marzo in 1999. However, there is no clear opinion on the subject of existence of dependencies between changes of the inflammatory type and PCa. MATERIAL AND METHODS: The study involved 1,010 men, suspected of prostate cancer development by positive digital rectal examination (DRE) and/or elevated PSA value. The 10 cores, TRUS guided biopsy was performed. In those with ASAP, HG–PIN or inflammation the second biopsy was proposed. RESULTS: In the first biopsy PCa was diagnosed in 336 patients (33.27%). ASAP was found in 58 (5.74%), HG–PIN in 82 (8.11%), and the coexistence of both was found in 19 (1.88%). Chronic prostatitis was diagnosed in 101 (10%) men. Of those who underwent second biopsy, PCa was diagnosed in six of 19 patients (31.57%) who were diagnosed with HG–PIN in the first biopsy, in four of 40 (10%) with BPH in the first biopsy, in four of 18 (22.22%) with ASAP or LG–PIN together with ASAP, and in two out of five (40%) with the coexistence of ASAP and HG–PIN. Malignancy was not confirmed in any of the patients in whom the diagnosis of BPH, HG–PIN, or ASAP was accompanied by chronic prostatitis. CONCLUSIONS: Chronic prostatitis does not significantly increase the value of PSA in patients with benign changes (BPH). The presence of prostatitis in the first biopsy did not predict cancer in subsequent biopsy, because the second biopsy did not reveal prostate cancer in any of the patients in whom prostatitis was diagnosed in the first biopsy.